A junctional cAMP compartment regulates rapid Ca2+ signaling in atrial myocytes. (April 2022) - Brandenburg, Sören; Pawlowitz, Jan; Steckmeister, Vanessa; Subramanian, Hariharan; Uhlenkamp, Dennis; Scardigli, Marina; Mushtaq, Mufassra; Amlaz, Saskia I.; Kohl, Tobias; Wegener, Jörg W.; Arvanitis, Demetrios A.; Sanoudou, Despina; et al.
Abstract: Axial tubule junctions with the sarcoplasmic reticulum control the rapid intracellular Ca 2+ -induced Ca 2+ release that initiates atrial contraction. In atrial myocytes we previously identified a constitutively increased ryanodine receptor (RyR2) phosphorylation at junctional Ca 2+ release sites, whereas non-junctional RyR2 clusters were phosphorylated acutely following β-adrenergic stimulation. Here, we hypothesized that the baseline synthesis of 3′, 5′-cyclic adenosine monophosphate (cAMP) is constitutively augmented in the axial tubule junctional compartments of atrial myocytes. Confocal immunofluorescence imaging of atrial myocytes revealed that junctin, binding to RyR2 in the sarcoplasmic reticulum, was densely clustered at axial tubule junctions. Interestingly, a new transgenic junctin-targeted FRET cAMP biosensor was exclusively co-clustered in the junctional compartment, and hence allowed to monitor cAMP selectively in the vicinity of junctional RyR2 channels. To dissect local cAMP levels at axial tubule junctions versus subsurface Ca 2+ release sites, we developed a confocal FRET imaging technique for living atrial myocytes. A constitutively high adenylyl cyclase activity sustained increased local cAMP levels at axial tubule junctions, whereas β-adrenergic stimulation overcame this cAMP compartmentation resulting in additional phosphorylation of non-junctional RyR2 clusters. Adenylyl cyclase inhibition, however, abolished the junctional RyR2 phosphorylation and decreased L-type Ca 2+ channel currents, while FRET imaging showed a rapid cAMP decrease. In conclusion, FRET biosensor imaging identified compartmentalized, constitutively augmented cAMP levels in junctional dyads, driving both the locally increased phosphorylation of RyR2 clusters and larger L-type Ca 2+ current density in atrial myocytes. This cell-specific cAMP nanodomain is maintained by a constitutively increased adenylyl cyclase activity, contributing to the rapid junctional Ca 2+ -induced Ca 2+ release, whereas β-adrenergic stimulation overcomes the junctional cAMP compartmentation through cell-wide activation of non-junctional RyR2 clusters. Graphical abstract: Schematic representation of constitutively increased local cAMP synthesis and Ca 2+ fluxes in the junctional compartment of atrial myocytes. A Epac1-based FRET cAMP biosensor fused to the cytosolic junctin N-terminus (Epac1-JNC), expressed in transgenic mice, demonstrates for the first time constitutively augmented cAMP pools in the dyadic cleft of atrial myocytes. (A) At baseline, adenylyl cyclase (AC) activity is constitutively high inside the dyadic cleft, sustaining increased local cAMP levels (FRET decreased) and activating the holoenzyme protein kinase A (PKA holo). The atria-specific cAMP-rich junctional compartment promotes the local PKA phosphorylation of RyR2 channel clusters, priming the rapid baseline Ca 2+ release flux. Additionally, the augmented junctional cAMP sustains the local PKA phosphorylation and dissociation of the small G-protein Rad, presumably increasing L-type Ca 2+ channel (LTCC) currents and increased Ca 2+ influx. Together, both the increased LTCC currents and RyR2 Ca 2+ release flux thus synergize the rapid activation of Ca 2+ -induced Ca 2+ release predominantly at axial tubule junctions in atrial myocytes. Indeed, confocal FRET measurements revealed augmented local junctional cAMP levels, explaining the sustained PKA phosphorylation exclusively of junctional but not non-junctional RyR2 channel clusters together with increased LTCC currents under baseline non-stimulated conditions in atrial myocytes. (B) Pharmacological inhibition of sustained adenylyl cyclase activity by MDL-12, 330A (MDL) in unstimulated atrial myocytes acutely decreased the junctional cAMP synthesis (FRET increased), the constitutively sustained RyR2 channel phosphorylation at baseline, and the LTCC Ca 2+ currents presumably through Rad binding and inhibition of the channel β2 -subunit. These MDL inhibitory actions thus decrease junctional Ca 2+ influx and SR Ca 2+ release as indicated by thin arrows. CSQ2, calsequestrin-2; JNC, junctin; JP2, junctophilin-2; LTCC, L-type Ca 2+ channel; N, nucleus; RyR2, ryanodine receptor type 2; SR, sarcoplasmic reticulum; TRDN, triadin. Unlabelled Image Highlights: In atrial myocytes, the SR protein junctin co-localizes with RyR2 channel clusters at voluminous axial tubule junctions. A junctin-targeted FRET biosensor allows high-resolution monitoring of local cAMP changes at junctional RyR2 clusters. A constitutively increased adenylyl cyclase activity sustains high junctional cAMP levels in atrial myocytes. High local cAMP levels augment junctional activitory RyR2 phosphorylation and may disinhibit Rad-dependent LTCC activity.